2022
DOI: 10.15252/embj.2022111869
|View full text |Cite
|
Sign up to set email alerts
|

The disulfide catalyst QSOX1 maintains the colon mucosal barrier by regulating Golgi glycosyltransferases

Abstract: Mucus is made of enormous mucin glycoproteins that polymerize by disulfide crosslinking in the Golgi apparatus. QSOX1 is a catalyst of disulfide bond formation localized to the Golgi. Both QSOX1 and mucins are highly expressed in goblet cells of mucosal tissues, leading to the hypothesis that QSOX1 catalyzes disulfide‐mediated mucin polymerization. We found that knockout mice lacking QSOX1 had impaired mucus barrier function due to production of defective mucus. However, an investigation on the molecular level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 88 publications
0
23
1
Order By: Relevance
“…produced in mice lacking QSOX1, such that these animals were hypersensitive to induced colitis [21]. As described below, no evidence was found that QSOX1 introduces disulfide bonds in vivo into the major glycoproteins that make up mucus.…”
Section: Physiological Pathways Affected By Qsox1mentioning
confidence: 99%
See 4 more Smart Citations
“…produced in mice lacking QSOX1, such that these animals were hypersensitive to induced colitis [21]. As described below, no evidence was found that QSOX1 introduces disulfide bonds in vivo into the major glycoproteins that make up mucus.…”
Section: Physiological Pathways Affected By Qsox1mentioning
confidence: 99%
“…In vitro, QSOX1 oxidizes an intestinal mucus-associated lectin protein, ZG16 [51], but it is not yet known whether ZG16 is a physiological substrate of QSOX1 in vivo or how the ZG16 disulfide might contribute to mucus properties [59]. In contrast, QSOX1 was found to introduce disulfides into certain Golgi glycosyltransferases in the intestinal epithelium, with clear physiological consequences [21]. Specifically, the sialyltransferases (STs) St6gal1 and St3gal1, enzymes that introduce sialic acid into glycoproteins and glycolipids, were excessively reduced, and thus presumably inactive [60][61][62], in QSOX1 knockout (KO) mice [21].…”
Section: Physiological Pathways Affected By Qsox1mentioning
confidence: 99%
See 3 more Smart Citations